Here's the original question:

Let $(a_n)$ be bounded. Assume that $a_{n+1} \ge a_{n} - 2^{-n}$. Show that $(a_n)$ is convergent.

Okay, I know that if I can show that if the sequence is monotone, I can conclude that it is convergent. But I am not sure how to show that it is monotone.

I know that $$a_n \le a_{n+1} + \frac{1}{2^n} < a_{n+1} + \frac{1}{n}$$

It looks to me as if it is monotonically increasing but I'm quite not sure how to prove my claim. Any hints would be appreciated.


For all $n$, let $$b_n = a_n - 2^{1-n}.$$ Note that $$b_{n+1} \ge b_n \iff a_{n+1} - 2^{-n} \ge a_n - 2^{1-n} \iff a_{n+1} \ge a_n - 2^{-n},$$ which is true. Note also that $b_n$ is the sum of the bounded sequence $a_n$ and the convergent sequence $-2^{1 - n}$, and hence is bounded as well. Thus, $b_n$ converges by the monotone convergence theorem, and hence, by the algebra of limits, so does $a_n$.

  • $\begingroup$ How did you come up with $(b_n)$? $\endgroup$ – Ashish K May 27 '18 at 17:14
  • $\begingroup$ I summed $$\sum_{k=0}^{n-1} 2^k = 2 - 2^{1-n}.$$ The idea is that the difference between $a_{n+1} - a_n$ and $b_{n+1} - b_n$ should be $2^{-n}$. Originally I used $b_n = a_n + 2 - 2^{1-n}$, but the constant addition of $2$ was superfluous. $\endgroup$ – Theo Bendit May 27 '18 at 17:25

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.